Metal Guitarist Forums banner
1 - 19 of 19 Posts

·
I like turtles!
Joined
·
714 Posts
I absolutely hate proofs.

Seriously. Why do I have to prove even the most basic of steps of the equation.
a) That's hardly a 'proof' in the true sense.
b) If Einstein pulled e = mc² outta his ass without showing how he got there, no one would ever have believed him
c) Most maths proofs tend to skip the 'most basic steps' of the algebra.
d) Forget what your high school teachers told you about maths because they don't know what they were talking about.
 

·
It's not lupus.
Joined
·
1,685 Posts
a) That's hardly a 'proof' in the true sense.
b) If Einstein pulled e = mc² outta his ass without showing how he got there, no one would ever have believed him
c) Most maths proofs tend to skip the 'most basic steps' of the algebra.
d) Forget what your high school teachers told you about maths because they don't know what they were talking about.
It's been about 6 years since I've taken any sort of mathematics class. Trust me, I've long forgotten what I was taught in high school math.
 

·
Party Röcker
Joined
·
1,357 Posts
That's right, because there's more than one of them.

a) That's hardly a 'proof' in the true sense.
b) If Einstein pulled e = mc² outta his ass without showing how he got there, no one would ever have believed him
c) Most maths proofs tend to skip the 'most basic steps' of the algebra.
d) Forget what your high school teachers told you about maths because they don't know what they were talking about.
It's wonderful how easily we can tell people who have seen math from people who haven't, isn't it?

Jeff
 

·
Registered
Joined
·
374 Posts
Too bad it stops working for some numbers under 5 as a multiplier.
... care to elaborate?

Jeff
of course it works! you just need 6 fingers and one negative finger ;)

4 times 4:

x = 4
y = 4

based on the 'hand' logic, one could assume that:

if 0 fingers up equals 5, and 1 finger up equals 6, then -1 fingers up would equal 4:

-1 (fingers up) = x-5 = 4

or the other way around: if 5 fingers down equals 5, and 4 fingers down equals 6, then 6 fingers up must equal 4:

6 (fingers down) = 10-y = 4

so:

x * y = 10 * [ (x-5) + (y-5) ] + 1 * [ (10-x) * (10-y) ]
x * y = 10 * [ (4-5) + (4-5) ] +1 * [ (10-4) * (10-4)]
x * y = 10 * -2 + 1* 36
x * y = -20 + 36
x * y = 16 (= 4 * 4)
 

·
Engineer Bassist
Joined
·
355 Posts
of course it works! you just need 6 fingers and one negative finger ;)

4 times 4:

x = 4
y = 4

based on the 'hand' logic, one could assume that:

if 0 fingers up equals 5, and 1 finger up equals 6, then -1 fingers up would equal 4:

-1 (fingers up) = x-5 = 4

or the other way around: if 5 fingers down equals 5, and 4 fingers down equals 6, then 6 fingers up must equal 4:

6 (fingers down) = 10-y = 4

so:

x * y = 10 * [ (x-5) + (y-5) ] + 1 * [ (10-x) * (10-y) ]
x * y = 10 * [ (4-5) + (4-5) ] +1 * [ (10-4) * (10-4)]
x * y = 10 * -2 + 1* 36
x * y = -20 + 36
x * y = 16 (= 4 * 4)
I realized it says to imagine the negative/extra fingers to make others work. Sorry my imagination must have shut down :D
 
1 - 19 of 19 Posts
This is an older thread, you may not receive a response, and could be reviving an old thread. Please consider creating a new thread.
Top